Modelling the effects of temperature on the rates of seedling emergence and leaf appearance in legume cover crops - Qi, A.; Wheeler, T.R.; Keatinge, J.D.H.; Ellis, R.H.; Summerfield, R.J.; Craufurd, Peter Q. (1999)
Simple models of the growth and development of legume cover crops in di erent environments may aid the selection of species and genotypes most suitable for particular farming systems. The e ects of temperature and photoperiod on the daily rate of seedling emergence (1/t50%) and the rate of leaf appearance (leaves d71 ) were quanti®ed for 12 diverse legume cover crop species. Six tropical or subtropical species were grown in 12 combinations of mean temperature (16.8, 21.8 and 26.8 8C) and photoperiod (11.5, 12.5, 13.5 and 14.5 h d71 ). Another six genotypes of temperate species were grown in nine combinations of mean temperature (16.8, 21.8 and 26.8 8C) and photoperiod (12.5, 13.5 and 14.5 h d71 ). Durations from sowing to 50% seedling emergence (t50%) were recorded and the number of leaves on the main stem counted during early vegetative growth. Photoperiod did not a ect either 1/t50% or leaves d71 . However, the e ects of temperature, photoperiod response group (short-day or long-day response), genotype or species and their interactions were all signi®cant. An optimal temperature between 21.8 and 26.8 8C for leaves d71 was identi®ed for Vicia sativa, Vicia dasycarpa and Lupinus mutabilis. Below the optimum temperature, 1/t50% and leaves d71 were positive linear functions of temperature for all legume species except Vicia dasycarpa. Estimates of base temperature (Tb) and thermal time (y) for 1/t50% and leaves d71 were obtained for each legume cover crop from these functions. Common values of Tb were found within each photoperiod response group: 9 8C and 1 8C for 1/t50%, and 10 8C and 72 8C for leaves d71 for short-day and long-day species respectively. Di erences among species were represented by variant estimates of y. The practical consequences of the combined e ects of these values of Tb and y for selecting legume cover crops for particular farming systems are discussed.